Decentralizing Infrastructure Services : Lessons from the East Asia Experience - Muzzini, Elisa (World Bank, Washington, DC, 2012)
This document specifies, most east asian countries have increasingly shifted responsibilities for infrastructure services to subnational tiers of governments. Infrastructure service provision involves a broad set of functions, including setting investment priorities, building and operating infrastructure facilities, and financing capital and operation and maintenance requirements. The extent to which each of these functions is transferred to subnational agencies defines a country's decentralization approach for infrastructure services. Subnational governments also have significant leeway in deciding how to mobilize funds for infrastructure projects. The infrastructure projects focused in three countries China, Indonesia, and the Philippines. In China, the central government plays a prominent role in setting investment priorities across infrastructure sectors. Indonesia and the Philippines have adopted a big bang approach to infrastructure decentralization. The report concludes, despite the heterogeneous environments in which decentralization has been implemented in the three countries, important lessons can be learned by comparing how each has fared in promoting regional coordination and building accountability for infrastructure services in a decentralized environment.